Info and Index of the EDUCARE Journal, Issue of February 2017 - EDUCARE, Editor Journal (EDUCARE, 2017)
EDUCARE journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the educational studies in general and its various aspects. Analysis will be practical and rigorous in nature. The EDUCARE journal, with Print ISSN 1979-7877, was firstly published on 17 August 2008, in the context to commemorate the Independence Day in Indonesia. Since issues of February 2009 to February 2016, EDUCARE journal was organized by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press, as an academic publishing owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE journal is published twice a year, i.e. every August and February.Bandung, Indonesia: February 27, 2017.Prof. Dr. Haji Endang KomaraSecretary of Expert Board of ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia.Â